Pengaruh Metoda Ruqyah Terhadap Penurunan Derajat Kecemasan (Penelitian Quasi Experimental Pada Pasien Di Ruqyah X Cabang Bandung) - Risydah Fadilah (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2015)
From the observation of the patient in the hospital, many have tried a medical treatment, but in some cases that did not ease the pain. This conditions bring up an asumption that a medical treatment that have been done was not effective, because many patients have more than just an organic problem, but also a psychological problem. There is another treatment that use a religious approach that called ruqyah. The purpose of this was to know the effect of ruqyah method towards 20 patient‟s decrease level of anxiety in Ruqyah X, Bandung. Quasi experimental was used as method of this research with One Group Pretest-Posttest Design. The data was analyzed using Wilxocon(z) test. Result showed that Zhit = 3.21, phit = 0.0007, and trust level  = 0,05. That means, it can be concluded there was a decrease level of anxiety in patient that has anxiety problem in Ruqyah X.